Strengthening effects evaluation on fatigue damage of rib to deck joint in orthotropic steel deck. (March 2023) - Xin, Haohui; Liu, Jielin; Correia, Jose A.F.; Berto, Filippo; Veljkovic, Milan; Yang, Fei
Highlights: A lightweight CFRP prestressed reinforcement method for the rib to deck joint of orthotropic steel decks (OSDs) was proposed. The strengthening effects of various strengthening methods on the fatigue crack propagation of rib to deck joint in OSDs were compared. The reinforcement effect of the proposed CFRP prestressed reinforcement method on the rib to deck joints with different crack sizes was analyzed. Abstract: Strengthening fatigue damage of orthotropic steel decks (OSDs) needs to comprehensively consider the strengthening effect and the dead weight introduced during the strengthening process, especially for OSDs in super large-span bridges or old renovated bridges, where the dead weight cannot be significantly increased during repair and maintenance. This paper proposed a new CFRP prestressed reinforcement method, that does not significantly increase dead weight while effectively inhibiting fatigue crack growth. The strengthening effects of various strengthening methods on the fatigue crack propagation of rib to deck joint in OSDs were compared. Besides, the strengthening effects of different crack sizes were also analyzed. The results showed that the proposed method is effective in reducing fatigue damage at the rib to deck joint in OSDs.